KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SEGERI KABUPATEN PANGKEP - Ramli, Rahmawati; Najihah, Najihah (Journal of Islamic Nursing, 2019)
Abstract Globally in 2012, of all deaths, non-communicable diseases caused 68% deaths and the majority of premature deaths (82%) because non-communicable diseases occurred in countries with low and middle opinions. And of all non-communicable disease-related deaths, 46% came from cardiovascular disease . Long-term hypertension can cause a decline in cognitive function, which of course will greatly disrupt the quality of life of patients. The aim of the study was to determine the quality of life of elderly people with hypertension in the Work Area of Segeri Health Center, Pangkep Regency. This research method uses qualitative research with a focus on phenomenological approaches. The research instrument is the researcher himself. Determination of samples using purposive sampling technique. The results of this study found the quality of life of the elderly in terms of the physical aspects of the elderly experiencing physical problems that disrupt activities, psychological aspects that consider the disease to be acquired due to the aging process, social aspects namely the elderly have good social relations with neighbors, and environmental aspects that are comfortable and safe. It is expected to provide clear and complete information to elderly hypertensive patients and families about the care of elderly hypertension and how to treat hypertension.\ Keywords: Elderly, Quality of life, hipertension.